2009
DOI: 10.1016/j.taap.2009.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry identifies multiple organophosphorylated sites on tubulin

Abstract: Acute toxicity of organophosphorus poisons (OP) is explained by inhibition of acetylcholinesterase in nerve synapses. Low dose effects are hypothesized to result from modification of other proteins, whose identity is not yet established. The goal of the present work was to obtain information that would make it possible to identify tubulin as a target of OP exposure. Tubulin was selected for study because live mice injected with a nontoxic dose of a biotinylated organophosphorus agent appeared to have OP-labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…The crystal structure of the bovine tubulin heterodimer (Protein Data Bank code 1jff) identifies residues involved in contacts in the microtubule (Nogales et al, 1999). Chlorpyrifos oxon (CPO) labeled residues in the tubulin dimer were identified by mass spectrometry in previous publications (Grigoryan et al, 2008; Grigoryan et al, 2009), while those in polymerized microtubules are reported in the present work. …”
Section: Figures and Tablesmentioning
confidence: 66%
See 1 more Smart Citation
“…The crystal structure of the bovine tubulin heterodimer (Protein Data Bank code 1jff) identifies residues involved in contacts in the microtubule (Nogales et al, 1999). Chlorpyrifos oxon (CPO) labeled residues in the tubulin dimer were identified by mass spectrometry in previous publications (Grigoryan et al, 2008; Grigoryan et al, 2009), while those in polymerized microtubules are reported in the present work. …”
Section: Figures and Tablesmentioning
confidence: 66%
“…At these concentrations of chlorpyrifos oxon, alpha tubulin is covalently modified on about 40% of Tyr 83, 7% of Tyr 224, and 5% of Tyr 272, while beta tubulin is covalently modified on 10% of Tyr 59, 2% of Tyr 106, and 20% of Tyr 281 (Grigoryan et al, 2009). Some of these residues are involved in contacts between protofilaments and in GTP binding (Table 1), suggesting that their modification resulted in structurally altered polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Protein MS has been used with some OPs as a valuable tool to identify OP-conjugated proteins employing peptide mass fingerprinting to match the isolated proteins to protein sequences by analyzing the OP-protein conjugates of AChE and BuChE Sun and Lynn, 2009;Grigoryan et al, 2009;Doorn et al, 2001;Jennings et al, 2003;Kropp and Richardson., 2006;. Advances in protein MS have been most useful to identify not only the adduction but also the post inhibition processes such as reactivation or aging reactions (Grigoryan et al, 2009;Doorn et al, 2001;Jennings et al, 2003;Mangas et al, 2016a). Figure 7 shows the active center peptide (ACP) of AChE trypsin digested enzyme detected after inhibition of most of the activity with the OPs paraoxon, sarin and mipafox, The ACP with sarin aged was also detected (Mangas et al, 2016a).…”
Section: Mass Spectrometry (Ms) Studiesmentioning
confidence: 99%
“…In another study, albumin was studied; peptide fragments of human serum albumin were analyzed in response to chlorpyrifos oxon, dichlorvos, diisopropylfluorophosphate, and sarin. [50][51][52][53] Complexes of Ni, Co, and Fe, were evaluated for the OPs sensing, but Cu 2+ gave the best response indicating that the ligand had to accommodate enough vacancy. Thus, at this early point it was concluded that "copper complexes may adsorb and desorb phosphorus esters in air."…”
Section: Mass Spectrometricmentioning
confidence: 99%